Flow-radiation coupling for atmospheric entries using a Hybrid Statistical Narrow Band model. (September 2016) - Soucasse, Laurent; Scoggins, James B.; Rivière, Philippe; Magin, Thierry E.; Soufiani, Anouar
Abstract: In this study, a Hybrid Statistical Narrow Band (HSNB) model is implemented to make fast and accurate predictions of radiative transfer effects on hypersonic entry flows. The HSNB model combines a Statistical Narrow Band (SNB) model for optically thick molecular systems, a box model for optically thin molecular systems and continua, and a Line-By-Line (LBL) description of atomic radiation. Radiative transfer calculations are coupled to a 1D stagnation-line flow model under thermal and chemical nonequilibrium. Earth entry conditions corresponding to the FIRE 2 experiment, as well as Titan entry conditions corresponding to the Huygens probe, are considered in this work. Thermal nonequilibrium is described by a two temperature model, although non-Boltzmann distributions of electronic levels provided by a Quasi-Steady State model are also considered for radiative transfer. For all the studied configurations, radiative transfer effects on the flow, the plasma chemistry and the total heat flux at the wall are analyzed in detail. The HSNB model is shown to reproduce LBL results with an accuracy better than 5% and a speed up of the computational time around two orders of magnitude. Concerning molecular radiation, the HSNB model provides a significant improvement in accuracy compared to the Smeared-Rotational-Band model, especially for Titan entries dominated by optically thick CN radiation. Abstract : Highlights: Developed Hybrid SNB (HSNB) model for flow-radiation coupling for hypersonic entries. Application to the FIRE 2 experiment (Earth) and the Huygens probe entry (Titan). HSNB model provides heat flux within 5% of LBL results and is 100 times faster.